An evaluation of different sites for measuring fat thickness in the beef carcass to determine carcass fatness - Johnson, E.R.; Vidyadaran, M.K. (CSIRO Publishing, 1981)
The accuracy of a single fat thickness measurement at each of five carcass sites and at the 10th and 12th ribs in estimating side fat weight and side fat percentage was determined in 36 steer carcasses. Three sites were associated with the fat layers of the split brisket, one was located at the caudodorsal angle of M. biceps femoris and one was situated 3.0 cm lateral to the highest point of the sacral crest. All three brisket sites were poor predictors of side fat weight and side fat percentage. The other four sites were of approximately equal accuracy in predicting side fat percentage, with residual standard deviations of: M. biceps femoris, 2.81%; sacral crest, 3.07%; 10th rib, 3.12%; and 12th rib, 2.81%. Side fat weight was predicted less accurately by M. biceps femoris (5.42 kg) than by sacral crest (4.50 kg), 10th rib (4.98 kg) or 12th rib (4.94 kg). Chilled side weight was a valuable addition in multiple regression analyses, significantly improving the residual standard deviations of all four sites, especially M, biceps femoris, in predicting side fat weight (M. biceps femoris, 1.56 kg; sacral crest, 3.54 kg; 10th rib, 3.31 kg; 12th rib, 2.84 kg). Only in the case of M. biceps femoris did the addition of chilled side weight improve the accuracy of prediction of side fat percentage (residual standard devation = 1.75%). The reliability of the seven sites in accurately measuring fat thickness was determined in 3215 dressed carcasses in six abattoirs. Sacral crest was clearly the most useful site. In addition to being an accurate predictor of carcass fat, it could be measured accurately in 98.3% of carcasses (or 94.3% of sides), compared with 10th rib (83.9% and 71.6% respectively) and 12th rib (82.9% and 68.5% respectively). If the measurement of fat thickness at the 12th rib is used in the Australian Beef Carcase Classification Scheme, up to 21% of carcasses (or up to 44% of sides) in some abattoirs will require alternative procedures to describe their fat status. Sacral crest fat thickness accurately estimated side fat weight and side fat percentage, and it provided reliable measurement in all but 1.7% of carcasses; it is conveniently located if an alternative site to the 12th rib is required.